Green tourism: Killhope, Lochranza Youth Hostel - Nicholas, Andrea (Henry Stewart Talks, 2020)
This case study looks at two tourism-based businesses that have taken measures to become more sustainable, and the ways it has affected their business as well as their surrounding communities.